Pengembangan Buku Ajar Sejarah Fisika Berbasis ICT - Lia Anggraeni; Boisandi Boisandi; Matsun Matsun (Universitas Hamzanwadi, 2019)
This study aims to determine: (1) The feasibility of ICT-based Physics History textbooks according to material experts, (2) The feasibility of ICT-based Physics History textbooks according to media experts. The research method used is R&D with reference to the 4-D model (four D model). The 4-D model consists of the define, design, development and disseminate stages. The development of ICT-based Physics History textbooks is the development of textbooks that help students in building information (knowledge) in understanding concepts through ICT in e-books in Physics History courses delivered. This is in accordance with KKNI curriculum planning, where the implementation of learning in the classroom is carried out with the Scientific Approach approach which includes observing, questioning, experimenting, associating (discussion), and networking (presentation). The results of the study are as follows: (1) ICT-Based Physics History Teaching books that have been validated by material experts with appropriate performance with an average value of 78, (2) ICT-Based Physics History Teaching books that have been validated by media experts with expertise suitable for use with an average rating of 80.